Cross-ideological coalitions under authoritarian regimes: Islamist-left collaboration among Morocco's excluded opposition. Issue 7 (2nd October 2020) - Casani, Alfonso
ABSTRACT: The 2011 popular uprisings across the MENA region demonstrated the organization of broad cross-ideological collaborations that were able to overcome some of the political cleavages that have traditionally characterized these societies, and more remarkably, the division between left-wing and Islamist actors. However, political tensions soon arose in the new post-uprising scenarios, with secularist-Islamist polarization increasing once again across the region. Contrary to this trend, Morocco saw an increase in collaboration between the opposition Left and Islamist movements. This article delves into the reasons why the opposition in Morocco has been able to avoid polarization, with, instead, an increase in cross-ideological coalitions opposing the regime. To that end, it analyses the rapprochement between the Islamist association Al-Adl wa-l-Ihsane and the country's left-wing parties, more noticeably the Democratic Way party. It argues that it is due to the excluded nature of these actors and their lack of electoral interests, that they have overcome political pressures and found new forms of collaboration. By drawing on an extensive corpus of in-depth interviews carried out in the Rabat-Casablanca region, this article examines the development of cross-ideological coalitions in the Moroccan opposition, while contributing, more broadly, to the study of cross-ideological coalitions under authoritarian regimes.